2008
DOI: 10.1128/jvi.00903-08
|View full text |Cite
|
Sign up to set email alerts
|

CAPERα Is a Novel Rel-TAD-Interacting Factor That Inhibits Lymphocyte Transformation by the Potent Rel/NF-κB Oncoprotein v-Rel

Abstract: The Rel/NF-B family of transcription factors is key for immune and inflammatory responses and also controls cell proliferation and apoptosis. The v-Rel oncoprotein of reticuloendotheliosis virus strain T (Rev-T) is the most potent oncogenic member of this family. Both v-Rel and its cellular homologue c-Rel transform primary splenic lymphocytes in vitro and cause fatal leukemia/lymphomas in chickens and transgenic mice (5,9,17,22,23,33,38,39). This agrees with the implication of Rel/NF-B in the pathogenesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 51 publications
0
44
0
Order By: Relevance
“…22 In a separate study, CAPER has also been shown to interact with the C-terminal transactivation domain (TAD) of the NF-κB oncoprotein v-Rel and to suppress its transforming activity in vitro. 23 However, the region of CAPER involved in the co-activation of v-Rel was shown to be different than the one involved in the co-activation of ERα/β and c-Jun. 23 In fact, v-Rel was reported to interact with the N-terminal domain of CAPER, while ERα/β and c-Jun interact with its C-terminal domain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…22 In a separate study, CAPER has also been shown to interact with the C-terminal transactivation domain (TAD) of the NF-κB oncoprotein v-Rel and to suppress its transforming activity in vitro. 23 However, the region of CAPER involved in the co-activation of v-Rel was shown to be different than the one involved in the co-activation of ERα/β and c-Jun. 23 In fact, v-Rel was reported to interact with the N-terminal domain of CAPER, while ERα/β and c-Jun interact with its C-terminal domain.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, the region of CAPER involved in the co-activation of v-Rel was shown to be different than the one involved in the co-activation of ERα/β and c-Jun. 23 In fact, v-Rel was reported to interact with the N-terminal domain of CAPER, while ERα/β and c-Jun interact with its C-terminal domain. 23 Interestingly, CAPER expression was also recently shown to be upregulated in human colorectal adenomas and carcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2F; Loerch et al 2014). These three proteins function in alternative splicing (Page-McCaw et al 1999;Lallena et al 2002;Dowhan et al 2005;Hastings et al 2007;Huang et al 2012); PUF60 and CAPERα also are coactivators of transcription (Liu et al 2000(Liu et al , 2001Jung et al 2002;Dowhan et al 2005;Dutta et al 2008). Other UHM-containing proteins participate in related pathways.…”
Section: Introductionmentioning
confidence: 99%